2021
DOI: 10.1002/ajim.23254
|View full text |Cite
|
Sign up to set email alerts
|

The role of nonstandard and precarious jobs in the well‐being of disabled workers during workforce reintegration

Abstract: Background: Nonstandard employment arrangements are becoming increasingly common and could provide needed flexibility for workers living with disabilities.However, these arrangements may indicate precarious employment, that is, employment characterized by instability, powerlessness, and limited worker rights and benefits. Little is known about the role of nonstandard and precarious jobs in the well-being of disabled persons during workforce reintegration after permanent impairment from work-related injuries or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…Many of these indicators of job precarity may be tied to beneficial or adaptive employment choices or easing into elective retirement; nevertheless, they may have an impact on reinjury risk. Workers age 65+ did not significantly differ from younger workers regarding several measures of occupational health and safety vulnerability sometimes used to indicate job precarity, 61,62 including comfort with reporting an unsafe work situation, reporting a work injury, or filing a WC claim. These issues related to job precarity will require further research to untangle.…”
Section: Discussionmentioning
confidence: 89%
“…Many of these indicators of job precarity may be tied to beneficial or adaptive employment choices or easing into elective retirement; nevertheless, they may have an impact on reinjury risk. Workers age 65+ did not significantly differ from younger workers regarding several measures of occupational health and safety vulnerability sometimes used to indicate job precarity, 61,62 including comfort with reporting an unsafe work situation, reporting a work injury, or filing a WC claim. These issues related to job precarity will require further research to untangle.…”
Section: Discussionmentioning
confidence: 89%
“…Administrative data included age, gender, WC coverage (State Fund vs. self-insured employer), and residence county, which was classified using the six-level 2013 National Center for Health Statistics Urban–Rural Classification Scheme for Counties (Ingram & Franco, 2014). All other covariates were obtained from the survey, and their collection and construction have been described in detail elsewhere (Edmonds et al, 2021; Sears, Edmonds, et al, 2021; Sears, Schulman, et al, 2021b, 2021c).…”
Section: Methodsmentioning
confidence: 99%
“…Our inclusion of workers with any type of permanent impairment enhances generalizability to a broad range of injuries and conditions. Limitations to generalizability include: (a) the survey being conducted only in English and (b) a high prevalence of union membership (42.2%), more than double the estimated 19.8% for Washington State in 2018 (Bureau of Labor Statistics), which may indicate relatively low job precarity among this sample (Edmonds et al, 2021). This was an exploratory study; more research is needed to replicate and extend these findings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…These pioneering US studies explored ways to align available data with EQ dimensions identified in European studies, i.e., [ 10 ]. For example, the dimension of interpersonal power relations has been operationalized with US data as union membership [ 25 ], intimidation about reporting occupational injury and safety concerns [ 31 ], the ability to control one’s schedule [ 16 , 32 ], decision-making power and autonomy on the job [ 16 , 25 , 27 ], experiences of sexual or other types of harassments [ 16 ], and forced retirement among older workers [ 32 ]. Many of these indicators could represent other EQ dimensions as well, such as employment stability (i.e., forced retirement), work time arrangements (i.e., schedule control), collective organization (i.e., union membership), and workers ’ rights (i.e., reporting safety concerns).…”
Section: Power As a Key To Conceptualizing Eqmentioning
confidence: 99%
“…The ubiquitous nature of power dynamics poses a challenge to conceptualizing and measuring EQ. At this early stage of EQ research in the United States, researchers have prioritized causal inferences, or showing the association between poor EQ and poor health, e.g., [ 16 , 31 ], and identifying who is at risk, e.g., [ 27 , 32 ]. This type of research has introduced and legitimized the concept of EQ in the discussion of occupational and population health in the United States.…”
Section: Power As a Key To Conceptualizing Eqmentioning
confidence: 99%